Platelet Phaeresis for Component Therapy in Dhaka Medical College- A Study of 26 Procedures (Journal of Medicine, 2008)
Platelet separation by aphaeresis machine from single donor was started in Blood Transfusion Department of Dhaka Medical College Hospital, from 10th April 2002. This study includes 26 procedures done in this dept. from the period of 10th April 2002 to 4th June 2003. Observation showed that demand of platelet came from different wards for different types of diseases such as , for Dengue- 8 cases, for Aplastic anaemia-2 cases, for Ovarian tumour-2 cases, for Caesarian section post operative DIC -2 cases, for AML with low platelet count -3 cases, for IUD with low platelet count -1 case, for Blood cancer -1 case , for NHL chemotherapy induced thrombocytopenia- 1 case , for Dengue Shock Syndrome - 1 case , 5 units donated in Shishu Hospital . Platelet was supplied according to group specific of the patient. Such as, 12 cases were O +ve, 10 cases were B +ve ,3 cases were A+ve and 1 case was AB+ve.      DOI = 10.3329/jom.v8i2.1407 J MEDICINE 2007; 8 : 53-56